Determination of the most significant fault parameters for Manila Trench earthquake tsunami - Aziz A.F.; Mardi N.H.; Malek M.A.; Tan W.K.; Teh S.Y. (Science Publishing Corporation Inc, 2023)
Manila Trench subduction zone is capable to produce high magnitude of earthquake event that can generate a deadliest tsunami disaster. The 2006 tsunami source workshop conducted by United States Geological Survey (USGS) had classified Manila Trench as the most hazardous potential earthquake generated tsunami source in South China Sea. The giant megathrust rupture from Manila Trench has the ability to create an earthquake as powerful as the Great Tohoku tsunami in 2011 and the Indian Ocean tsunami in 2004. This technical paper aims to review the fault parameters used by different researchers in investigating the possibility of tsunami occurrences generated from Manila Trench earthquake to the coastal areas of Terengganu, Malaysia which is located within the vicinity of South China Sea. The selected fault parameters were simulated by using TUNA model in order to study the potential effects of Manila Trench earthquake induced tsunami. The outcomes of the simulation are the wave height and wave arrival time. At the end of this technical paper, an intensive approach is implemented to select the most significant fault parameters that create the potential worst-case tsunami scenario towards Terengganu coastal areas in terms of the highest and fastest first wave arrived. 2018 Authors.